SAE Technical Paper Series 2009
DOI: 10.4271/2009-01-1878
|View full text |Cite
|
Sign up to set email alerts
|

Possible Influence of High Injection Pressure on Diesel Fuel Stability: A Review and Preliminary Study

Abstract: Recent developments in diesel engines and fuel injection equipment combined with the change to ULSD and bio-blends have resulted in increased reports regarding deposits within injectors and filters. A review of known fuel degradation mechanisms and other relevant chemistries suggests the effects of high pressure and high shear environments should be examined as the most probable causes of increasing deposit formation. Existing fuel quality tests do not correlate with reported fouling propensity. Analytical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The reports of deposits continue to grow and their origins summarised in figure 1 more complex. These origins have been discussed in the literature on several occasions The production of carbonaceous deposits from the degradation of fuel by injector temperature and pressure increases in recent years in conjunction with the ability of newly introduced ULSD to solubilise deposit forming material was discussed first in 2009 [1]. Recently studies of corrosion in the infrastructure of the fuel supply chain, have also found acetic acid in fuels [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The reports of deposits continue to grow and their origins summarised in figure 1 more complex. These origins have been discussed in the literature on several occasions The production of carbonaceous deposits from the degradation of fuel by injector temperature and pressure increases in recent years in conjunction with the ability of newly introduced ULSD to solubilise deposit forming material was discussed first in 2009 [1]. Recently studies of corrosion in the infrastructure of the fuel supply chain, have also found acetic acid in fuels [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The CEC is developing test methods to address the issue. Many technical papers have been recently published describing work on a number of investigations into the character and origins of internal diesel injector deposits (IDID) [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. What is clear is that there is not a single outcome or cause.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum was recorded directly from the injector needle using a Nicolet ^^^μ^ι microscope in conjunction with a Nexus bench. It is noteworthy that in a previous study [5] that this reference fuel after clay filtration did not produce any deposit with low molecular weight PIBSI. Further, since the original infrared spectrum of low molecular weight PIBSIs shows only some amide presence then the amide part of the deposit formed has to be the result of reaction with acidic species in the fuel.…”
Section: Engine Testmentioning
confidence: 61%
“…Increased emissions from the plugging of spray holes was found in 1991 [3], and increased emissions legislation forced changes in fuel and engine design [3,4]. Recent changes in fuel properties such as solubilsing ability [5] caused for example by the introduction of ULSD and the introduction of more stringent emission regulations along with the increased tolerances, temperatures and pressures in modern diesel injector systems has seen the formation of internal injector deposits (IDID). Thus, more than ever there is a need for high quality, effective DCAs.…”
Section: Introductionmentioning
confidence: 99%